An innovative proposal for legal learning from an interdisciplinary perspective: The protection of fundamental rights against the exercise of the state's ius puniendi - López Espejo, Julia; Morales Moreno, África María (Revista Jurídica de Investigación e Innovación Educativa (REJIE Nueva Época), 2025)
This article aims to highlight the implementation of a teaching innovation activity within the framework of a training programme for new teachers at the University of Cordoba. The objective is to bring students closer to the practical reality through two fundamental ideas: the transversality of fundamental rights in the Spanish legal system and the interdisciplinary nature of different areas of Law. To this end, the activity has been divided into different phases, including a visit to the Constitutional Court and the resolution of a case study that integrates the protection of fundamental rights, criminal Law, and sanctioning tax Law. In this way, the aim is to explain the development of this activity, present the results achieved and share the main difficulties detected during and after its execution, so that this analysis contributes to the introduction of improvements for future editions of the activity.